The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0079198
|View full text |Cite
|
Sign up to set email alerts
|

Dogs’ Eavesdropping from People’s Reactions in Third Party Interactions

Abstract: Eavesdropping involves the acquisition of information from third-party interactions, and can serve to indirectly attribute reputation to individuals. There is evidence on eavesdropping in dogs, indicating that they can develop a preference for people based on their cooperativeness towards others. In this study, we tested dogs’ eavesdropping abilities one step further. In a first experiment, dogs could choose between cooperative demonstrators (the donors) who always gave food to an approaching third person (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…Marshall-Pescini et al (2011), Freidin et al (2013), and Nitzschner et al (2014) used a similar food sharing situation as described for non-human primates. Although the results of the experiment by Marshall-Pescini et al (2011) showed that dogs prefer the prosocial human partner over the antisocial partner, the latter two studies suggested that dogs’ choice was influenced by the location of the human (in the test situation) rather than the identity and behavior.…”
Section: Comparative Approach To Social Evaluationmentioning
confidence: 99%
“…Marshall-Pescini et al (2011), Freidin et al (2013), and Nitzschner et al (2014) used a similar food sharing situation as described for non-human primates. Although the results of the experiment by Marshall-Pescini et al (2011) showed that dogs prefer the prosocial human partner over the antisocial partner, the latter two studies suggested that dogs’ choice was influenced by the location of the human (in the test situation) rather than the identity and behavior.…”
Section: Comparative Approach To Social Evaluationmentioning
confidence: 99%
“…Play is not unique in this respect: playful interactions appear to be just one of several different contexts in which dogs can observe and assess other dogs' behavioural traits and strategies (e.g. Kundey et al, 2011;Marshall-Peschini et al, 2011), although precisely what information dogs extract from observing such third-party interactions is still unclear (Freidin et al, 2013).…”
Section: "Eavesdropping" During Dog-human Playmentioning
confidence: 99%
“…Conversely, dogs (Canis lupus familiaris) descend from wolves (Canis lupus), which live in family groups and engage in group hunting and alloparenting [10], thus they are highly social and cooperative. Furthermore, dogs were domesticated by humans-they can cooperate with humans and rely on them for valuable resources [11], such as food and shelter. Thus, it would be beneficial for dogs to observe humans interacting with each other or with other dogs and gain information from such an exchange to select the most appropriate person with whom to associate and whom to avoid.…”
Section: Introductionmentioning
confidence: 99%
“…This was not controlled for in Marshall-Pescini, Passalacqua, Ferrario, Valsecchi and Prato-Previde's [15] study. Therefore, Freidin, Putrino, D'Orazio and Bentosela [11] and Nitzschner, Kaminski, Melis and Tomasello [16] tested this hypothesis by swapping the generous and selfish experimenters' positions before the dogs could choose which experimenter to approach. Their results showed that dogs chose the experimenter on the side where the food interaction had previously happened [16] or chose at random [11], suggesting that results from previous studies could be largely explained by local enhancement.…”
Section: Introductionmentioning
confidence: 99%